Fashion as an event: Conservation and its digital (dis)contents. Issue 1 (1st June 2019) - Scaturro, Sarah
Fashion conservators face documentation challenges specific to the very nature of fashion objects, including their fragile and ephemeral materialities, three-dimensionality and inherently mutable forms. Conservation documentation is, in this sense, central to the definition of an object in a museum, moving beyond its practical and bureaucratic function of capturing an object's current state and the treatment undertaken to address its problems.This article presents an insight into the work of the conservator and reflects on the different issues connected to digital and non-digital documentation practices within a fashion museum. It explores the ways in which a fashion conservator generates technical documentation to capture information regarding the methods of an object's creation and what might have been done to it before it entered the museum. What is this archive of conservation documentation and how is it made? Who uses it and what do they do with it? How do conservators document fashion and are they successful in capturing its temporal values? This article provides answers to these questions, exploring an overlooked practice and readdressing the agency of the fashion conservator in the definition of fashion in the museum.